The Effect of Water Weed (Pistia stratiotes) Bokashi on The Growth of Pakcoy (Brassica rapa L.) - Makaruku, Marlita Herlin; Tanasale, Vilma Laurien; Kembauw, Esther; Wattimena, Anna Yuliana; Goo, Nureny (International Journal of Multidisciplinary Sciences and Arts, 2023)
Fertilizers are very important nutrients added to plants. Bokashi fertilizer is an organic fertilizer that is very useful when applied to plants because it contains beneficial microorganisms that are able to provide plant nutrients through the recycling process and form a soil structure that is suitable for plant growth. This study aimed to determine the growth of pakcoy (Brassica rapa L.) by the application of water weed (Pistia stratiotes) bokashi. The research method used a Randomized Block Design (RBD) of two factors with three replications. The treatment factors consisted of water weed (Pistia stratiotes) bokashi doses of P0, P1, P2 and P3 (0, 10, 20, and 30 ton.ha-1), and bokashi time application of T1, T2 and T3 (14 days before planting, 7 days before planting, at the same time as planting). The size of the plot is 1 m × 1 m and in 1 plot there are 12 plants. Data observed in this study consisted of growth variables analysed using Analysis of Variance and continued with the Duncan’s Multiple Range Test (DMRT) at ? = 5%. Results of this study showed that the dose of bokashi water weed (Pistia stratiotes) treatment was 20 ton.ha-1 (P2), bokashi time application was 7 days before planting (T2), and the interaction gave a very significant effect on all growth observation variables including plant length, number of leaves, and area leaf.